A linguagem documentária no âmbito da representação da informação arquivística - Wanderley, Ana Isabel Ferreira (2019)
It deals with the construction of a documentary language directed to the representative treatment of archival information of the Federal University of Ceará (UFC). The general objective was to analyze the applicability of Cervantes “Integrated Methodological Model for Thesaurus Construction” for the representation of archival information at the Federal University of Ceará. Specific objectives were defined: to investigate the theoretical and methodological foundations of the representation of archival information; investigate the relationship between archival classification and indexing; map the terminology adopted in the archival documentation regarding UFC people management; and build a documentary language based on Cervantes' “Integrated Methodological Model for Thesaurus Construction”, for the representation of archival information. To achieve the proposed objectives, an applied and descriptive research was conducted, supported by a qualitative approach. The scientific inquiry is based on the archival documentation produced by the UFC regarding the management of people in the custody of the Archive Division. The corpus of the research was composed of 2014 procedural types related to dismissals, concessions and licenses, totaling 259 cases. Documentary research was carried out from three main sources: National Archives Council Classification Code, Law No. 8,112 / 1990, and UFC procedural types to collect information about the context of production of archival documents. Using the Content Analysis technique, from Bardin's perspective, to systematize and interpret the collected records, the Cervantes “Integrated Methodological Model for Thesaurus Construction” was applied to establish the equivalence, hierarchical and associative relationships between terms collected for the composition of a thesaurus. From this methodological proposal, the following results were obtained: although the main categories remain constant in the documentary sources examined, there are dissonances in the definitions of the subcategories of the studied themes, and there is imprecision in the terms used by the servers to formulate their requests, it is not clear how to define the nuances between remoteness, concessions and licenses. The procedural types generated by the UFC demonstrate that there is a dual difficulty: both for the servers to formulate their demands, as for the information professionals who perform the archival classification. What emerged from the analysis was a dichotomy between what is requested, how it is classified and what is in the legislation. It was observed that the multiplicity of looks on the same object can hinder the reach of a more integrated intersection between the macro and the micro universe of the University. Through the triangulation of the documentary sources, the categories and subcategories that formed the construction of the thesaurus under Cervantes bias were constituted. Cervantes' “Integrated Methodological Model for Thesaurus Construction” has been found to have practicality and flexibility elements that fit the specifics of the archival document, so that in conjunction with the classification activity it establishes additional access points that can be favor fast and efficient access to information. The flexibility of the Cervantes Model could also be proven by integrating harmoniously with Content Analysis. It is concluded that the model designed by Cervantes contributes to the archival representational process, especially in the organization of cross-references, focusing on the definition of relationships between the different languages employed in the federal public university.